2004
DOI: 10.1002/bsl.589
|View full text |Cite
|
Sign up to set email alerts
|

Association of serotonin transporter promoter gene polymorphism with violence: relation with personality disorders, impulsivity, and childhood ADHD psychopathology

Abstract: There is evidence that disturbances in central serotonin (5-HT) function have a role in impulsive aggression, violence, and criminality. A deletion/insertion polymorphism within the 5-HT transporter (5-HTT) promoter gene (5-HTT gene-linked polymorphic region, 5-HTTLPR) is thought to be associated with several psychopathological phenotypes related to disturbed impulse control, anxiety and depression. This study examined the association of the 5-HTTLPR with violent behavior in a sample of 153 male Caucasians ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
1
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(105 citation statements)
references
References 50 publications
(21 reference statements)
4
87
1
10
Order By: Relevance
“…Accordingly, 5HTT constitutes another candidate gene for violent behavior. A small, yet increasing number of studies also investigated the implications of 5HTT genotype on aggression and demonstrated an association between short 5HTT alleles and violent behavior (Gerra et al, 2004;Retz et al, 2004;Liao et al, 2004), although the latter study conveyed several problems as the polymorphism was not in Hardy-Weinberg equilibrium. Gene-environment interactions have not yet been examined in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, 5HTT constitutes another candidate gene for violent behavior. A small, yet increasing number of studies also investigated the implications of 5HTT genotype on aggression and demonstrated an association between short 5HTT alleles and violent behavior (Gerra et al, 2004;Retz et al, 2004;Liao et al, 2004), although the latter study conveyed several problems as the polymorphism was not in Hardy-Weinberg equilibrium. Gene-environment interactions have not yet been examined in humans.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] The relationship between impaired serotonergic function and aggression is well established. 26 One potential pathway by which the 5-HTTLPR gene is related to impulsivity and aggression is through observed alterations in amygdala function as the amygdala, along with the prefrontal cortex and orbital cortex, is thought to play a role in the emergence of violent behavior via faulty regulation of negative emotion.…”
Section: Serotonin Transportermentioning
confidence: 99%
“…23 Since then, many more groups have examined this gene in other behavioural disorders including anxiety-related traits, suicide, bipolar mood disorder, attention deficit hyperactivity disorder, impulsive aggressive behaviour and psychoticism. [24][25][26][27][28][29] Unfortu- …”
mentioning
confidence: 99%